2010
DOI: 10.1016/j.ygeno.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of COPA, Identified by Loss-of-Function Screen, Induces Apoptosis and Suppresses Tumor Growth in Mesothelioma Mouse Model

Abstract: Malignant mesothelioma is a highly aggressive tumor arising from serosal surfaces of the pleura and is triggered by past exposure to asbestos. Currently, there is no widely accepted treatment for mesothelioma. Development of effective drug treatments for human cancers requires identification of therapeutic molecular targets. We therefore conducted a large-scale functional screening of mesothelioma cells using a genome-wide small interfering RNA library. We determined that knockdown of 39 genes suppressed mesot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 18 publications
7
50
0
Order By: Relevance
“…S9 in the supplemental material). This apoptotic signature is consistent with the observation that the depletion of eIF4A3 and Y14, respectively, decreases cell growth (63) and promotes apoptosis in mouse mesothelioma cells (69). Depleting other RNA binding proteins that did not modulate Bcl-x splicing did not elicit apoptosis (see Table S1 and Fig.…”
Section: Components More Prevalently Associated With Ejc Function Affsupporting
confidence: 89%
See 1 more Smart Citation
“…S9 in the supplemental material). This apoptotic signature is consistent with the observation that the depletion of eIF4A3 and Y14, respectively, decreases cell growth (63) and promotes apoptosis in mouse mesothelioma cells (69). Depleting other RNA binding proteins that did not modulate Bcl-x splicing did not elicit apoptosis (see Table S1 and Fig.…”
Section: Components More Prevalently Associated With Ejc Function Affsupporting
confidence: 89%
“…(C) Annexin V assay in HeLa cells transfected with siRNAs targeting EJC components. Cells were immunostained for annexin V (red), and nuclei were labeled with Hoechst stain (blue) (69). The percentage of apoptotic cells was quantitated (bottom graph) upon transfection of siRNAs targeting eIF4A3, Y14, and RNPS1 (2 siRNAs each) and compared to that for various controls (Lipofectamine alone, negative-control siRNAs targeting KITLG and cyclin D1, and a positive-control siRNA targeting KIF11 [71]).…”
Section: Discussionmentioning
confidence: 99%
“…One report has shown that EIF3D is relatively stable and could be a reliable reference gene for assessing gene expression in nasopharyngeal cancer [22]. On the contrary, another study in the same year has reported that EIF3D may be involved in the anti-apoptosis and tumorigenesis of mesothelioma [23]. In the present study, we add a new finding to the function of EIF3D in PCa.…”
Section: Discussionsupporting
confidence: 47%
“…Recently, eIF3d is continually described in cancers. Sudo et al [18] firstly identified eIF3d as one of genes involved in mesothelioma cell viability using a genome-wide small interfering RNA library, suggesting that eIF3d may have the potential of a diagnostic marker and a therapeutic target of mesothelioma. eIF3d, eIF3e, eIF3f, eIF3h and eIF4b have been identified to be up-regulated in gastric cancer patients with acquired resistance to cisplatin and fluorouracil (CF) [19].…”
Section: Introductionmentioning
confidence: 99%